MiR-320d Inhibits Progression of EGFR-Positive Colorectal Cancer by Targeting TUSC3 - Yufeng, Zhu; Ming, Qi; Dandan, Wu (Frontiers in Genetics, 2021)
Background: The mechanism of miR-320d in EGFR-positive colorectal cancer (CRC) has not been fully elucidated. The aim of the present study was to explore the molecular mechanism of miR-320d in CRC. Methods: The miRNA microarray analysis was conducted to identify differential expressed miRNAs. The expression of miR-320d was validated using Quantitative real-time PCR. EGFR-positive CRC cells were transfected with miR-320d mimic and inhibitor, after which cell proliferation, migration and invasion were assayed. The relationship between miR-320d and TUSC3 was confirmed using bioinformatics and dual-luciferase reporter gene assays. Proteins involved in signaling pathways and the epithelial-mesenchymal transition were detected with western blot. Results: We found that the miR-320d expression is associated with tumor size and distant metastasis in colorectal cancer. Overexpression of miR-320d in EGFR-positive HCT-116 and SW480 cells decreased not only the proliferation ability but also the invasion and migration ability. In addition, miR-320d had the ability to inhibit epithelial-to-mesenchymal transition. Luciferase assays revealed that miR-320d directly targets the 3'-UTR of TUSC3. TUSC3 was downregulated by miR-320d at both the protein and mRNA levels in EGFR-positive CRC cell lines. Conclusion: Generally, our results demonstrated that miR-320d could inhibit the malignant phenotype of EGFR-positvie CRC through targeting TUSC3. The miR-320d might be a potential therapeutic target for EGFR-positvie CRC.